Electrifying India : regional political economies of development - Kale, Sunila S., 1973- (Stanford University Press, 2014)
Throughout the 20th century, electricity was considered to be the primary vehicle of modernity, as well as its quintessential symbol. In India, electrification was central to how early nationalists and planners conceptualized Indian development, and huge sums were spent on the project from then until now. Yet despite all this, sixty-five years after independence nearly 400 million Indians have no access to electricity. Electrifying India explores the political and historical puzzle of uneven development in India's vital electricity sector. In some states, nearly all citize.